Heart failure in haemoglobinopathies: pathophysiology, clinical phenotypes, and management. (20th December 2016) - Farmakis, Dimitrios; Triposkiadis, Filippos; Lekakis, John; Parissis, John
Abstract: Hereditary haemoglobinopathies, mainly beta‐thalassemia and sickle cell disease, constitute the most common monogenic disorders in humans, and although once geographically confined, they are currently globally distributed. They are demanding clinical entities that require multidisciplinary medical management. Despite their genotypic and phenotypic heterogeneity, the haemoglobinopathies share several similarities in pathophysiology, clinical manifestations, therapeutic requirements, and complications, among which heart failure (HF) represents a leading cause of mortality and morbidity. However, haemoglobinopathies have generally been addressed in a rather fragmentary manner. A unifying approach focusing on the underlying similarities of HF attributes in the two main entities might contribute to their better understanding, characterization, and management. In the present review, we attempt such an approach to the pathophysiology, clinical phenotypes, and management of HF in haemoglobinopathies.